Pulmonary Resistance Modification under treatment with Sacubitril/valsartan in Patients with Heart Failure with reduced ejection fraction (PRESENT-HF) - Study protocol and rationale for a multicentre randomised controlled trial - Straburzyńska-Migaj, Ewa; Dudek, Magdalena; Migaj, Jacek; Bartczak-Rutkowska, Agnieszka; Hiczkiewicz, Jarosław; Cygański, Piotr; Tycińska, Agnieszka; Gierlotka, Marek; Kozielska-Nowalany, Ewa; Kubica, Jacek; Tomaszewska, Małgorzata; Sawiński, Piotr; et al. (Journal of Medical Science, 2025)
Introduction. Heart failure with reduced ejection fraction (HFrEF) remains a major clinical challenge, partly due to suboptimal implementation of guideline-directed medical therapy and complications such as pulmonary hypertension (PH) that worsen symptoms and prognosis.Material and methods. PRESENT-HF (ClinicalTrials.gov Identifier: NCT05487261, https://clinicaltrials.gov/ct2/show/NCT05487261) is a multicenter, randomised, double-blind, comparator-controlled clinical trial investigating whether sacubitril/valsartan, compared to enalapril, lowers pulmonary artery pressure and pulmonary vascular resistance as measured by right heart catheterisation in patients with HFrEF and secondary PH. The study will recruit approximately 230 patients, with a 1:1 randomisation to either sacubitril/valsartan or enalapril, and a 52-week follow-up that includes both in-hospital and out-of-hospital treatment phases.Results. The primary endpoint is the change from baseline in mean pulmonary artery pressure and pulmonary vascular resistance; secondary outcomes include clinical events, quality of life, functional capacity, and safety.Conclusions. This trial will offer new insights into targeted strategies for improving outcomes in patients with HFrEF complicated by PH, potentially expanding treatment options and informing future guidelines.
Keywords: HFrEF; ARNI; sacubitril/valsartan; pulmonary hypertension; pulmonary hypertension due to left heart disease